Formação inicial de professores: contribuição da disciplina LIBRAS para futuros professores da educação básica - Jesus, Liana Fabíola de (2017)
The research entitled "Initial Teacher Training: contribution of the Libras discipline to the future teachers of basic education" highlights a actual theme in the context of inclusive education for deaf education in primary education, after the recognition of the Brazilian Sign Language as the second official language in Brazil. With the introduction of Libras in the curricula of undergraduate courses, we see the need for this discipline to provide the academic (future teacher) with elements that qualify him for his performance in the classroom. The challenges that this professional will encounter in the exercise of teaching with a deaf student may be: communication barrier, understanding of the deaf culture, teaching methodologies that met the educational needs of these students, etc. In view of this context, which is to train teachers to work in educational diversity, we ask: How is the offering of the Libras discipline contributing to the formation of the teacher of Basic Education for the teaching of deaf students? We propose to identify how the Libras discipline and the resources contained therein are contributing to the initial formation of teachers to work with deaf students in the basic education network in three public HEIs in the city of Manaus, as well as: Institutions and courses selected disciplines that address issues involving special and / or inclusive education and Libras; To analyze the Pedagogical Projects of Courses (PPCs) and the menus of the Disciplines Special Education and Libras in three courses of degrees offered by the public HEIs and VERIFY the perception of academics and teachers as to the level of relevance of the Libras discipline as well as its impact on the initial training of future teachers in the selected institutions; Presentation of a proposal to revise the menu of the Libras discipline for Higher Education Institutions that offer undergraduate courses. For the development of this research we use the methodology exploratory beyond the bibliographical research. As an instrument of data collection, questionnaires, both for the training teachers who teach the Discipline Libras and for academics who attended said discipline. The results indicate absence of practical work in two Higher Education Institutions or even the challenge of emulating the students to make reflection / action / reflection, also, we understand that it is urgent to align theory with practice, favoring the emergence of Contributions that may help in the pedagogical work, whose research needs to be put into practice with theories, according to the existing educational reality and suggest improvements, actions, methods and materials that can positively impact the learning of those students in need of a differentiated approach . To finalize this study, we elaborated a didactic and functional proposal, which resulted in a Product titled: Revised Proposal of the Ples Discipline Menu for undergraduate courses, duly expanded and revised, with significant alteration of content and workload, both theoretical and practical , Unfolding it in two complementary disciplines and, of course, the first one presents itself as a prerequisite of the second, for its complementarity, with the intention of contributing to the improvement of the initial formation of the future teacher.